Application of bacteriophage in rapid detection of Escherichia coli in foods. (June 2021) - Wang, Jun; Kanach, Andrew; Han, Rongwei; Applegate, Bruce
Abstract : Food is a common vehicle for introducing Escherichia coli into humans which can result in serious disease. Efficient and rapid detection of E. coli in the multitude of food and beverage matrices available is critical to limit the health, financial, and social impacts of these infections. Compared to culture-based and molecular detection methods, bacteriophage-based detection methods perform favorably with high specificity, natural affinity, low cost, and reliable live-dead cell distinction. More recently, many rapid bacteriophage-based detection approaches have been developed coupled with advanced techniques including fluorescence, immunology, molecular biology, nanoscale science, and an array of biosensing strategies. In this review, up-to-date applications and principles of bacteriophage-based detection methods for E. coli in food are discussed, in addition to their current limitations and future prospects.